Seed storage - Chin, H.F.; Hanson, Jean (CAB International, 1999)
Seeds of legumes and grasses have become increasingly important as planting materials to establish forages for animal production in the tropics and subtropics. Availability of high-quality seeds of adapted and productive forage species is essential for successful pasture establishment. However, shortage of good-quality seeds is one of the major constraints to increasing the area sown to forages, especially in tropical regions of the world. This paper discusses factors affecting seed viability during storage; storage characteristics of forage seeds; seed packaging; storage pests; seed storage facilities; storage during transport; on farm storage; and bulk storage in warehouses.